2012
DOI: 10.2164/jandrol.112.016865
|View full text |Cite
|
Sign up to set email alerts
|

Penile Veins Are the Principal Component in Erectile Rigidity: A Study of Penile Venous Stripping on Defrosted Human Cadavers

Abstract: The human erectile mechanism is an intricate interplay of hormonal, vascular, neurological, sinusoidal, pharmacological, and psychological factors. However, the relative influence of each respective component remains somewhat unclear, and merits further study. We investigated the role of venous outflow in an attempt to isolate the key determinant of erectile function. Dynamic infusion cavernosometry and cavernosography was conducted on 15 defrosted human cadavers, both before and after the systematic removal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 57 publications
0
11
0
5
Order By: Relevance
“…Clinically refined PVS benefits most impotent males (Hsu et al ., ). This belief was further supported after a couple of recent studies on fresh and defrosted human cadavers, while a fully rigid erection was readily attainable and maintainable after penile erection‐related veins were thoroughly stripped and ligated closest to the tunica albuginea (Hsieh et al ., ; Hsu et al ., ). An easier intracorporeal fluid retention was reported by those who were not satisfied with PVS alone.…”
Section: Discussionmentioning
confidence: 97%
“…Clinically refined PVS benefits most impotent males (Hsu et al ., ). This belief was further supported after a couple of recent studies on fresh and defrosted human cadavers, while a fully rigid erection was readily attainable and maintainable after penile erection‐related veins were thoroughly stripped and ligated closest to the tunica albuginea (Hsieh et al ., ; Hsu et al ., ). An easier intracorporeal fluid retention was reported by those who were not satisfied with PVS alone.…”
Section: Discussionmentioning
confidence: 97%
“…In tandem with a better understanding of penile venous anatomy, painstaking studies have been carried out on defrosted and fresh cadavers to omit the psychological impact on penile erection . Investigators concluded that penile veins are crucial in attaining a rigid erection . Renovation of the venous anatomy of the penis has inspired the latest refinement of venous surgery.…”
Section: Penile Venous Surgerymentioning
confidence: 99%
“…23 Investigators concluded that penile veins are crucial in attaining a rigid erection. [112][113][114] Renovation of the venous anatomy of the penis has inspired the latest refinement of venous surgery. Hsu et al resorted to an even more radical technique, refined penile venous stripping, achieved using local anesthesia as an ambulatory surgery.…”
Section: Penile Venous Surgerymentioning
confidence: 99%
“…[17][18][19] Bu venlerin ereksiyonda esas etkili venler oldu¤u gösterilmitir. [20,21] Derin venler; V. cavernosa (v. profunda penis), fascia profunda'nın altında ayrı bir ba¤ dokusu perivasküler kılıfın içinde tunica albuginea'ya yakın olarak, v. dorsalis profunda penis ile a. dorsalis profunda penis arasında bulunurlar (ekil 1). V. cavernosa'lar, v. emisseria'lar aracılı¤ı ile corpus cavernosum'lardan, kanı drene ederler.…”
Section: Pen‹s Venler‹unclassified